2001
DOI: 10.1051/parasite/200108s2136
|View full text |Cite
|
Sign up to set email alerts
|

Detection of coproantigen in early trichinellosis

Abstract: Summary :Trichinellosis has become undoubtedly worldwide in distribution. Its diagnosis relies largely on the serodiagnostic procedures which are of great value but unfortunately miss the enteric phase. This could be a serious diagnostic problem in the absence of corresponding epidemiological data and typical symptoms and signs of the disease. In this study the possibility of coproantigen detection, as an early diagnostic aid in trichinellosis, was investigated in mice experimentally infected with Trichinella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Accordingly, if simplified and inexpensive protocols are developed, the immunologic detection of hookworm coproantigens may represent an attractive diagnostic alternative to fecal egg assays. Coproantigen ELISAs have previously been reported for nematodes such as Haemonchus contortus 25 and Teladorsagia circumcincta 26 in sheep, Ostertagia ostertagi in cattle, 27 Heligmosomoides polygyrus 28 and Trichinella spiralis 29 in mice, and Strongyloides ratti in rats. 30 However, to our knowledge this is the first report of the technique being applied to the diagnosis and evaluation of experimental hookworm infection.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, if simplified and inexpensive protocols are developed, the immunologic detection of hookworm coproantigens may represent an attractive diagnostic alternative to fecal egg assays. Coproantigen ELISAs have previously been reported for nematodes such as Haemonchus contortus 25 and Teladorsagia circumcincta 26 in sheep, Ostertagia ostertagi in cattle, 27 Heligmosomoides polygyrus 28 and Trichinella spiralis 29 in mice, and Strongyloides ratti in rats. 30 However, to our knowledge this is the first report of the technique being applied to the diagnosis and evaluation of experimental hookworm infection.…”
Section: Discussionmentioning
confidence: 99%
“…Trichinosis remains an important zoonotic foodborne parasitic disease, affecting man and many other mammals, of worldwide distribution (Boulos et al 2001). The pig is the main source of infection to man.…”
Section: Introductionmentioning
confidence: 99%
“…probably because at this stage all worms have already been expelled and the larvae have already reached the tissues. These results were confirmed by Boulos., et al [4] who suggested that the detected antigen could…”
Section: Discussionmentioning
confidence: 99%
“…Capture ELISA was used for the determination of Trichinella coproantigen using T. spiralis Antigen Detection-Microwell ELISA [4,20].…”
Section: Trichinella Spiralis Infectionmentioning
confidence: 99%
See 1 more Smart Citation